Extending Financial Portfolio Theory for Product Management - Leong, S. M. (Institutional Knowledge at Singapore Management University, 1991)
A multiperiod portfolio framework is proposed to modify financial portfolio theory for application in product portfolio decisions. This framework should help marketers in allocating scarce corporate resources to various competing products as well as contribute to developing a body of theory to solve an important problem in marketing management. Its multiperiod nature forces marketing planners to determine: 1. the appropriate time horizon for planning evaluation, 2. strategic and product-specific constraints on the risks and returns on projects over time, and 3. total and individual project capital budgets and feasible investment levels over the planning horizon. The framework considers that investment decisions may be costly and that returns may be affected by the level of investment due to imperfections or economies of scale in the product market. The proposed model can be further generalized to consider, for example, the effects of macroeconomic variables